A Survey on Existing CAPTCHA Techniques and Proposed Gaming CAPTCHA for Better Security Analysis - Kumar, Vipin; Barve, Atul (International Journal of Computer Sciences and Engineering, 2025)
CAPTCHA (Completely Automated Public Turing test to tell Computers and Humans Apart) is a method which is used to identify whether user is robot or human. For security concern it is required to know by using some kind of Turing Test. Traditionally, distorted letters in non-uniform positions are generally used for this test, because it has been considered that, it is easy to analyze the distorted letters by human which cannot by robot or bots. But later it could also be recognized by robot, then various research has been made, based on 3d alphanumeric letters, numerical calculations, moving alphanumeric letters, OTP & gaming. But some time distorted letters, 3d letters & moving alphabets are also difficult to recognize by human, it becomes irritating. And numerical calculation is often become easy now by robot, based on neural networks & OTP[4] takes longer time because it is depend on mobile network, so that is why these techniques are also not convenient for human. It should be very easy for human and almost impossible by robots. Then a new promising way was introduced i.e. gaming based CAPTCHA, it is most attractive and cognitive way in the world of CAPTCHA. This is the most recent method used by various personals. But the game which is used for is static, it means you will have to drag & drop static object to the given static target which may be breakable by some intelligent systems. So, that is why here it is the solution which proposes a dynamic object & target gaming based CAPTCHA, it means that here the target is not static as well as object, you will have to drag & drop moving object to moving target which is considered as impossible for robot in given time, because we are also using a CAPTCHA session, you will get 10-15 seconds to achieve your goal and it can be achieved by 5 to 8 seconds by human or may be less. But not possible by robot because after given session time another CAPTCHA will be appeared to achieve.